The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4314/bajopas.v4i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allelochemicals of Some Eucalyptus Species on Germination and Radicle Growth of <i>Arachis Hypogea</i>

Abstract: A laboratory experiment was conducted to assess the effects of allelochemicals of Eucalyptus camaldulensis, Eucalyptus citriodora and Eucalyptus globules on germination and root elongation using leguminous crop ground nut ( Arachis hypogea) as bioassay material. The experiments were conducted in sterilized petridishes. The effect of different concentration of aqueous extracts was compared with distilled water (control). The result revealed that different concentrations of E. globulus and E. camaldulensis extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
1
0
0
2
Order By: Relevance
“…. Changes in DNA synthesis, mitochondrial metabolism, and cell mitotic indices contribute to the inhibition of root growth and development, consistent with ndings byLawan et al, (2011). The higher sensitivity of roots to allelochemicals compared to aerial parts of seedlings has been reported in various studies(Bughio et al, 2013;Das & Bandyopadhyay, 2011;Ercoli et al, 2007;Florence, 1986;Jafari et al, 2004).…”
supporting
confidence: 85%
“…. Changes in DNA synthesis, mitochondrial metabolism, and cell mitotic indices contribute to the inhibition of root growth and development, consistent with ndings byLawan et al, (2011). The higher sensitivity of roots to allelochemicals compared to aerial parts of seedlings has been reported in various studies(Bughio et al, 2013;Das & Bandyopadhyay, 2011;Ercoli et al, 2007;Florence, 1986;Jafari et al, 2004).…”
supporting
confidence: 85%
“…Although the allelochemicals were shown either to be stimulatory or inhibitory in the first tranche of experiments, i.e., Petri plate experiments (PPEs), the results revealed that higher concentrations (6%, 8%, and 10%) of aqueous extracts significantly inhibited the germination of both crops, i.e., C. arietinum and T. aestivum. Lawan et al [33], Vashishth et al [34] and Khattak et al [35] have also reported similar findings. The allelochemicals found in aqueous extracts of Jatropha curcas were found to be stimulatory to wheat at lower concentrations, while at higher concentrations, the extracts were either inhibitory or did not affect wheat plant growth compared with the control.…”
Section: Seed Germinationmentioning
confidence: 54%
“…En contraste, Murillo et al (2005), registran que los extractos hexánicos de E. globulus tiene un efecto alelopático negativo sobre el crecimiento de la soya, el tomate y la lechuga. Lawan et al (2011) registraron el potencial negativo del eucalipto afectando la longitud radicular de Arachis hypogaea L. hasta en un 50.4% con extractos acuosos (45 g/L) durante 120 horas. Los bioensayos desarrollados en Cusco en concentraciones de 10, 25, 50, 100 y 1,000 mg/L, son coincidentes con Castro-Moreno y Chong-Rodríguez (2015) y difieren de los resultados obtenidos por Murillo et al (2005) y Lawan et al (2011), aun cuando en Cusco se trabajó con concentraciones menores, pero, durante un tiempo mayor.…”
Section: Discussionunclassified
“…Lawan et al (2011) registraron el potencial negativo del eucalipto afectando la longitud radicular de Arachis hypogaea L. hasta en un 50.4% con extractos acuosos (45 g/L) durante 120 horas. Los bioensayos desarrollados en Cusco en concentraciones de 10, 25, 50, 100 y 1,000 mg/L, son coincidentes con Castro-Moreno y Chong-Rodríguez (2015) y difieren de los resultados obtenidos por Murillo et al (2005) y Lawan et al (2011), aun cuando en Cusco se trabajó con concentraciones menores, pero, durante un tiempo mayor. Ballester et al (1982), realizaron cuatro ensayos utilizando extractos de hojas de eucalipto y acículas de pino, para determinar los efectos alelopáticos en la germinación de semillas de Trifolium repens L., Trifolium pratense L., Di chondra repens J.R. Forst.…”
Section: Discussionunclassified